Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Rapid water quality change in the E lwha R iver estuary complex during dam removal - Melissa M. Foley; Jeffrey J. Duda; Matthew M. Beirne; Rebecca Paradis; Andrew Ritchie; Jonathan A. Warrick (Limnology and Oceanography, 2015)
Dam removal in the United States is increasing as a result of structural concerns, sedimentation of reservoirs, and declining riverine ecosystem conditions. The removal of the 32 m Elwha and 64 m Glines Canyon dams from the Elwha River in Washington, U.S.A., was the largest dam removal project in North American history. During the 3 yr of dam removal—from September 2011 to August 2014—more than ten million cubic meters of sediment was eroded from the former reservoirs, transported downstream, and deposited throughout the lower river, river delta, and nearshore waters of the Strait of Juan de Fuca. Water quality data collected in the estuary complex at the mouth of the Elwha River document how conditions in the estuary changed as a result of sediment deposition over the 3 yr the dams were removed. Rapid and large‐scale changes in estuary conditions—including salinity, depth, and turbidity—occurred 1 yr into the dam removal process. Tidal propagation into the estuary ceased following a large sediment deposition event that began in October 2013, resulting in decreased salinity, and increased depth and turbidity in the estuary complex. These changes have persisted in the system through dam removal, significantly altering the structure and functioning of the Elwha River estuary ecosystem.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Mind the gap: how do climate and agricultural management explain the ‘yield gap’ of croplands around the world? - Rachel Licker; Matt Johnston; Jonathan A. Foley; Carol Barford; Christopher J. Kucharik; Chad Monfreda; Navin Ramankutty (Global Ecology and Biogeography, 2010)
Aim As the demands for food, feed and fuel increase in coming decades, society will be pressed to increase agricultural production – whether by increasing yields on already cultivated lands or by cultivating currently natural areas – or to change current crop consumption patterns. In this analysis, we consider where yields might be increased on existing croplands, and how crop yields are constrained by biophysical (e.g. climate) versus management factors. Location This study was conducted at the global scale. Methods Using spatial datasets, we compare yield patterns for the 18 most dominant crops within regions of similar climate. We use this comparison to evaluate the potential yield obtainable for each crop in different climates around the world. We then compare the actual yields currently being achieved for each crop with their ‘climatic potential yield’ to estimate the ‘yield gap’. Results We present spatial datasets of both the climatic potential yields and yield gap patterns for 18 crops around the year 2000. These datasets depict the regions of the world that meet their climatic potential, and highlight places where yields might potentially be raised. Most often, low yield gaps are concentrated in developed countries or in regions with relatively high‐input agriculture. Main conclusions While biophysical factors like climate are key drivers of global crop yield patterns, controlling for them demonstrates that there are still considerable ranges in yields attributable to other factors, like land management practices. With conventional practices, bringing crop yields up to their climatic potential would probably require more chemical, nutrient and water inputs. These intensive land management practices can adversely affect ecosystem goods and services, and in turn human welfare. Until society develops more sustainable high‐yielding cropping practices, the trade‐offs between increased crop productivity and social and ecological factors need to be made explicit when future food scenarios are formulated.

Crop planting dates: an analysis of global patterns - William J. Sacks; Delphine Deryng; Jonathan A. Foley; Navin Ramankutty (Global Ecology and Biogeography, 2010)
Aim To assemble a data set of global crop planting and harvesting dates for 19 major crops, explore spatial relationships between planting date and climate for two of them, and compare our analysis with a review of the literature on factors that drive decisions on planting dates. Location Global. Methods We digitized and georeferenced existing data on crop planting and harvesting dates from six sources. We then examined relationships between planting dates and temperature, precipitation and potential evapotranspiration using 30‐year average climatologies from the Climatic Research Unit, University of East Anglia (CRU CL 2.0). Results We present global planting date patterns for maize, spring wheat and winter wheat (our full, publicly available data set contains planting and harvesting dates for 19 major crops). Maize planting in the northern mid‐latitudes generally occurs in April and May. Daily average air temperatures are usually c . 12–17 °C at the time of maize planting in these regions, although soil moisture often determines planting date more directly than does temperature. Maize planting dates vary more widely in tropical regions. Spring wheat is usually planted at cooler temperatures than maize, between c . 8 and 14 °C in temperate regions. Winter wheat is generally planted in September and October in the northern mid‐latitudes. Main conclusions In temperate regions, spatial patterns of maize and spring wheat planting dates can be predicted reasonably well by assuming a fixed temperature at planting. However, planting dates in lower latitudes and planting dates of winter wheat are more difficult to predict from climate alone. In part this is because planting dates may be chosen to ensure a favourable climate during a critical growth stage, such as flowering, rather than to ensure an optimal climate early in the crop's growth. The lack of predictability is also due to the pervasive influence of technological and socio‐economic factors on planting dates.

Challenges to estimating carbon emissions from tropical deforestation - NAVIN RAMANKUTTY; HOLLY K. GIBBS; FRÉDÉRIC ACHARD; RUTH DEFRIES; JONATHAN A. FOLEY; R. A. HOUGHTON (Global Change Biology, 2007)
An accurate estimate of carbon fluxes associated with tropical deforestation from the last two decades is needed to balance the global carbon budget. Several studies have already estimated carbon emissions from tropical deforestation, but the estimates vary greatly and are difficult to compare due to differences in data sources, assumptions, and methodologies. In this paper, we review the different estimates and datasets, and the various challenges associated with comparing them and with accurately estimating carbon emissions from deforestation. We performed a simulation study over legal Amazonia to illustrate some of these major issues. Our analysis demonstrates the importance of considering land‐cover dynamics following deforestation, including the fluxes from reclearing of secondary vegetation, the decay of product and slash pools, and the fluxes from regrowing forest. It also suggests that accurate carbon‐flux estimates will need to consider historical land‐cover changes for at least the previous 20 years. However, this result is highly sensitive to estimates of the partitioning of cleared carbon into instantaneous burning vs. long‐timescale slash pools. We also show that carbon flux estimates based on ‘committed flux’ calculations, as used by a few studies, are not comparable with the ‘annual balance’ calculation method used by other studies.

A model of carbon evasion and sedimentation in temperate lakes - Paul C. Hanson; Amina I. Pollard; Darren L. Bade; Katie Predick; Stephen R. Carpenter; Jonathan A. Foley (Global Change Biology, 2004)
Lakes process terrigenous carbon. The carbon load processed by lakes may partially offset estimates made for terrestrial net ecosystem exchange ( NEE ). The balance within lakes between carbon burial and evasion to the atmosphere determines whether lakes are net sinks or net sources of atmospheric carbon. Here we develop a model to study processing of both autochthonous and allochthonous carbon sources in lakes. We run the model over gradients of dissolved organic carbon ( DOC ) and total phosphorus ( TP ) concentrations found in the Northern Highlands Lake District of Wisconsin. In our model, lakes processed between 5 and 28 g C m −2 (watershed) yr −1 derived from the watershed, which approximates one‐tenth of NEE for similar terrestrial systems without lakes. Most lakes were net heterotrophic and had carbon evasion in excess of carbon burial, making them net sources of carbon to the atmosphere. Only lakes low in DOC and moderate to high in TP were net autotrophic and net sinks of carbon from the atmosphere.

Effects of logging on carbon dynamics of a jack pine forest in Saskatchewan, Canada - Erica A. Howard; Stith T. Gower; Jonathan A. Foley; Christopher J. Kucharik (Global Change Biology, 2004)
We calculated carbon budgets for a chronosequence of harvested jack pine ( Pinus banksiana Lamb.) stands (0‐, 5‐, 10‐, and∼29‐year‐old) and a∼79‐year‐old stand that originated after wildfire. We measured total ecosystem C content (TEC), above‐, and belowground net primary productivity (NPP) for each stand. All values are reported in order for the 0‐, 5‐, 10‐, 29‐, and 79‐year‐old stands, respectively, for May 1999 through April 2000. Total annual NPP (NPP T ) for the stands (Mg C ha −1 yr −1 ±1 SD) was 0.9±0.3, 1.3±0.1, 2.7±0.6, 3.5±0.3, and 1.7±0.4. We correlated periodic soil surface CO 2 fluxes ( R S ) with soil temperature to model annual R S for the stands (Mg C ha −1 yr −1 ±1 SD) as 4.4±0.1, 2.4±0.0, 3.3±0.1, 5.7±0.3, and 3.2±0.2. We estimated net ecosystem productivity (NEP) as NPP T minus R H (where R H was calculated using a Monte Carlo approach as coarse woody debris respiration plus 30–70% of total annual R S ). Excluding C losses during wood processing, NEP (Mg C ha −1 yr −1 ±1 SD) for the stands was estimated to be −1.9±0.7, −0.4±0.6, 0.4±0.9, 0.4±1.0, and −0.2±0.7 (negative values indicate net sources to the atmosphere.) We also calculated NEP values from the changes in TEC among stands. Only the 0‐year‐old stand showed significantly different NEP between the two methods, suggesting a possible mismatch for the chronosequence. The spatial and methodological uncertainties allow us to say little for certain except that the stand becomes a source of C to the atmosphere following logging.

Regime Shifts in the Sahara and Sahel: Interactions between Ecological and Climatic Systems in Northern Africa - Jonathan A. Foley; Michael T. Coe; Marten Scheffer; Guiling Wang (Ecosystems, 2003)

Influence of Geoengineered Climate on the Terrestrial Biosphere - Vaishali Naik; Donald J. Wuebbles; Evan H. DeLucia; Jonathan A. Foley (Environmental Management, 2003)

The global distribution of cultivable lands: current patterns and sensitivity to possible climate change - Navin Ramankutty; Jonathan A. Foley; John Norman; Kevin McSweeney (Global Ecology and Biogeography, 2002)
Aim This study makes quantitative global estimates of land suitability for cultivation based on climate and soil constraints. It evaluates further the sensitivity of croplands to any possible changes in climate and atmospheric CO 2 concentrations. Location The location is global, geographically explicit. Methods The methods used are spatial data synthesis and analysis and numerical modelling. Results There is a cropland ‘reserve’ of 120%, mainly in tropical South America and Africa. Our climate sensitivity analysis indicates that the southern provinces of Canada, north‐western and north‐central states of the United States, northern Europe, southern Former Soviet Union and the Manchurian plains of China are most sensitive to changes in temperature. The Great Plains region of the United States and north‐eastern China are most sensitive to changes in precipitation. The regions that are sensitive to precipitation change are also sensitive to changes in CO 2 , but the magnitude is small compared to the influence of direct climate change. We estimate that climate change, as simulated by global climate models, will expand cropland suitability by an additional 16%, mainly in the Northern Hemisphere high latitudes. However, the tropics (mainly Africa, northern South America, Mexico and Central America and Oceania) will experience a small decrease in suitability due to climate change. Main conclusions There is a large reserve of cultivable croplands, mainly in tropical South America and Africa. However, much of this land is under valuable forests or in protected areas. Furthermore, the tropical soils could potentially lose fertility very rapidly once the forest cover is removed. Regions that lie at the margins of temperature or precipitation limitation to cultivation are most sensitive to changes in climate and atmospheric CO 2 concentration. It is anticipated that climate change will result in an increase in cropland suitability in the Northern Hemisphere high latitudes (mainly in developed nations), while the tropics will lose suitability (mainly in developing nations).

Measurements and Modeling of Carbon and Nitrogen Cycling in Agroecosystems of Southern Wisconsin: Potential for SOC Sequestration during the Next 50 Years - Christopher J. Kucharik; Kristofor R. Brye; John M. Norman; Jonathan A. Foley; Stith T. Gower; Larry G. Bundy (Ecosystems, 2001)

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Global-Scale Relationships between Climate and the Dengue Fever Vector, Aedes Aegypti - Marianne J. Hopp; Jonathan A. Foley (Climatic Change, 2001)

On the stability of the high‐latitude climate‐vegetation system in a coupled atmosphere‐biosphere model - Samuel Levis; Jonathan A. Foley; Victor Brovkin; David Pollard (Global Ecology and Biogeography, 1999)
Summary In order to investigate the hypothesis that the Earth's climate and vegetation patterns may have more than one basic state, we use the fully coupled GENESIS‐IBIS model. GENESIS is an atmospheric general circulation model. IBIS is a dynamic global vegetation model that integrates biophysical, physiological, and ecological processes. GENESIS and IBIS are coupled by way of a common land surface interface to allow for the full and transient interaction between changes in the vegetation structure and changes in the general circulation of the atmosphere. We examine two modern climate simulations of the coupled model initialized with two different initial conditions. In one case, we initialize the model vegetation cover with the modern observed distribution of vegetation. In the other case, we initialize the vegetation cover with evergreen boreal forests extending to the Arctic coast, replacing high‐latitude tundra. We interpret the coupled model's behaviour using a conceptual model for multistability and demonstrate that in both simulations the climate‐vegetation system converges to the same equilibrium state. In the present climate, feedbacks between land, ocean, sea ice, and the atmosphere do not result in the warming required to support an expanded boreal forest.

Estimating historical changes in land cover:North American croplands from 1850 to 1992 - Navin Ramankutty; Jonathan A. Foley (Global Ecology and Biogeography, 1999)
Summary 1. We present a simple algorithm for reconstructing spatially explicit historical changes in croplands. We initialize our simulation with a satellite‐derived characterization of present‐day croplands c. 1992. This data set of croplands is then used within a simple model, along with historical cropland inventory data at the national and subnational level, to reconstruct historical crop cover. We present an annual data set of cropland areas in North America between 1850 and 1992, at a spatial resolution of 5 min (≈10 km). 2. The reconstructed changes in North American crop cover are generally consistent with qualitative descriptions of change. Crop cover is initially concentrated in the eastern portions of the continent, and subsequently migrates westward into the Midwestern United States and the Prairie Provinces of Canada. We also see cropland abandonment in the eastern portions of the continent during the 20th century. The simulation, however, fails to characterize adequately the changes in crop cover in Mexico. 3. We also estimate the extent to which the different vegetation types of North America have been cleared for cultivation. We find that savannas/grasslands/steppes and forests/woodlands have undergone the most extensive conversion (1.68 and 1.40 million km 2 cleared, respectively, since 1850). We further discuss the wider implications of such large‐scale changes in land cover.

Coupling dynamic models of climate and vegetation - JONATHAN A. FOLEY; SAMUEL LEVIS; COLIN I. PRENTICE; DAVID POLLARD; STARLEY L. THOMPSON (Global Change Biology, 1998)

Coupling dynamic models of climate and vegetation - Jonathan A. Foley; Samuel Levis; I. Colin Prentice; David Pollard; Starley L. Thompson (Global Change Biology, 1998)
Numerous studies have underscored the importance of terrestrial ecosystems as an integral component of the Earth's climate system. This realization has already led to efforts to link simple equilibrium vegetation models with Atmospheric General Circulation Models through iterative coupling procedures. While these linked models have pointed to several possible climate–vegetation feedback mechanisms, they have been limited by two shortcomings: (i) they only consider the equilibrium response of vegetation to shifting climatic conditions and therefore cannot be used to explore transient interactions between climate and vegetation; and (ii) the representations of vegetation processes and land‐atmosphere exchange processes are still treated by two separate models and, as a result, may contain physical or ecological inconsistencies. Here we present, as a proof concept, a more tightly integrated framework for simulating global climate and vegetation interactions. The prototype coupled model consists of the GENESIS (version 2) Atmospheric General Circulation Model and the IBIS (version 1) Dynamic Global Vegetation Model. The two models are directly coupled through a common treatment of land surface and ecophysiological processes, which is used to calculate the energy, water, carbon, and momentum fluxes between vegetation, soils, and the atmosphere. On one side of the interface, GENESIS simulates the physics and general circulation of the atmosphere. On the other side, IBIS predicts transient changes in the vegetation structure through changes in the carbon balance and competition among plants within terrestrial ecosystems. As an initial test of this modelling framework, we perform a 30 year simulation in which the coupled model is supplied with modern CO 2 concentrations, observed ocean temperatures, and modern insolation. In this exploratory study, we run the GENESIS atmospheric model at relatively coarse horizontal resolution (4.5° latitude by 7.5° longitude) and IBIS at moderate resolution (2° latitude by 2° longitude). We initialize the models with globally uniform climatic conditions and the modern distribution of potential vegetation cover. While the simulation does not fully reach equilibrium by the end of the run, several general features of the coupled model behaviour emerge. We compare the results of the coupled model against the observed patterns of modern climate. The model correctly simulates the basic zonal distribution of temperature and precipitation, but several important regional biases remain. In particular, there is a significant warm bias in the high northern latitudes, and cooler than observed conditions over the Himalayas, central South America, and north‐central Africa. In terms of precipitation, the model simulates drier than observed conditions in much of South America, equatorial Africa and Indonesia, with wetter than observed conditions in northern Africa and China. Comparing the model results against observed patterns of vegetation cover shows that the general placement of forests and grasslands is roughly captured by the model. In addition, the model simulates a roughly correct separation of evergreen and deciduous forests in the tropical, temperate and boreal zones. However, the general patterns of global vegetation cover are only approximately correct: there are still significant regional biases in the simulation. In particular, forest cover is not simulated correctly in large portions of central Canada and southern South America, and grasslands extend too far into northern Africa. These preliminary results demonstrate the feasibility of coupling climate models with fully dynamic representations of the terrestrial biosphere. Continued development of fully coupled climate‐vegetation models will facilitate the exploration of a broad range of global change issues, including the potential role of vegetation feedbacks within the climate system, and the impact of climate variability and transient climate change on the terrestrial biosphere.